Adaptation of an evidence-based postpartum depression intervention: feasibility and acceptability of mothers and babies 1-on-1 - Darius Tandon, S. (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Mothers and Babies (MB) is a cognitive-behavioral intervention with demonstrated efficacy in reducing depressive symptoms and preventing depressive episodes among perinatal women when delivered in a group format by mental health professionals. Study aims were to describe the adaptation of MB into a 1-on-1 modality (MB 1-on-1) and provide data on the adapted intervention’s acceptability and feasibility. METHODS: Seventy-five home visitors trained on MB 1-on-1 delivered the 15-session intervention to 1–2 clients. Client acceptability data assessed intervention enjoyment, comprehension, and usefulness. Home visitor feasibility and acceptability data measured amount of intervention material delivered, client comprehension, and client engagement. RESULTS: Home visitors were all female with 8.8 years of experience on average. 117 clients completed acceptability surveys. Average client age was 21.9 years and 41% were pregnant. Home visitors completely covered 87.9% of sessions and reported clients totally understood MB material 82.5% of the time across sessions, although variability was found in comprehension across modules. 82.0% of clients found MB 1-on-1 enjoyable and 91.6% said they totally understood sessions, when averaged across sessions. Clients enjoyed content on noticing one’s mood and pleasant activities. Implementation challenges were client engagement, facilitating completion of personal projects, and difficulty shifting between didactic and interactive activities. CONCLUSIONS: Clients found MB 1-on-1 to be enjoyable, easily understood, and useful. Home visitors reported excellent implementation fidelity and felt clients understood MB material. A refined 12-session version of MB 1-on-1 should be examined for its effectiveness in reducing depressive symptoms, given encouraging feasibility and acceptability data. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12884-018-1726-0) contains supplementary material, which is available to authorized users.